ROA dan Stock Prices: Studi Komparatif pada PT Delta Djakarta Tbk., PT Indofood CBP Sukses Makmur Tbk., PT Ultrajaya Milk Industry dan Trading Company Tbk. - Novitasari, Yuli; Bunadi, Ilik; Hadianto, Ade Manggala (Lembaga Pengembangan Kinerja Dosen, 2025)
This study conducts a comparative analysis of the influence of Return on Assets (ROA) on the stock prices of three large companies in the consumer sector: PT Delta Djakarta Tbk. (DLTA), PT Indofood CBP Sukses Makmur Tbk. (ICBP), and PT Ultrajaya Milk Industry and Trading Company Tbk. (ULTJ), during the period 2018-2024. Using a quantitative approach with secondary data, this study applies panel data regression separately for each company, then compares the results. The research findings show that at PT Delta Djakarta Tbl. (DLTA, ROA has a positive influence on stock prices. However, for PT Indofood CBP Sukses Makmur Tbk. (ICBP) and PT Ultrajaya Milk Industry and Trading Company Tbk. (ULTJ), ROA is not the main factor determining stock price movements based on the analyzed data.